Executive authority, the personal vote, and budget discipline in Latin American and Carribean countries - Mark Hallerberg; Patrick Marier (Rheinische Friedrich-Wilhelms-Universität Bonn, Zentrum für Europäische Integrationsforschung (ZEI), 2001)
Recent scholarship on the impact of fiscal institutions on budgeting outcomes in Latin American and Caribbean (LAC) countries indicates that political institutions impact the level of budget discipline. BuiIding upon this previous research, we argue that the principle problem that must be addressed to insure strong fiscal discipline is the common pool resource (CPR) problem. The source of the problem, as well as its solution, differ in the government and in the legislature. At the cabinet level, the CPR problem arises because ministers consider the spending and tax implications of decisions on their ministries (only) instead of on the general population. As Hallerberg and von Hagen (1999) indicate, the appropriate solution at the cabinet level depends upon the coalition structure of the government. Given that all LAC countries have either presidential or oneparty parliamentary systems, a strong central player like the finance minister can reduce the CPR problem at the cabinet level. A similar strengthening of the executive vis-à-vis the legislature, in contrast, does not necessarily lead to tighter fiscal discipline. The level of the CPR problem in the legislature depends upon the type of electoral system. If states have open list proportional representation systems, then increases in district magnitude increase the problem, while under closed lists increases in district magnitude decrease the problem. Using a data set of LAC countries for the period 1988-97 and following Carey and Shugart (1995), we create an index for the incentives for the personal vote. We find that executive power in the budget process is most effective in reducing budget deficits when the personal vote is high in the legislature, while strengthening the president (or prime minister) in countries where the personal vote is low in the legislature has no statistically significant effect. This finding has practical implications for the design of fiscal institutions in LAC countries—granting the executive a privileged position vis-à-vis the legislature has beneficial effects on the budget balance only when the CPR problem in the legislature is large. Moreover, an alternative institutional change is to reform a country's electoral system. The second option may be more feasible in countries where legislators are unlikely to give the president more power, or where dictatorial pasts make populations wary of granting the executive too much authority on any policy area.
Keywords: 330; Finanzpolitik; Public Choice; Gruppenentscheidung; Allmenderessource; Lateinamerika; Karibische Staaten